Stories in light : a guide to the stained glass of the basilica at the University of Notre Dame - Cavadini, Nancy (University of Notre Dame Press, 2020)
Cover -- Half Title -- Title Page -- Copyright -- Dedication -- Contents -- Preface -- Basilica Floorplan -- Using This Guidebook -- CHAPTER ONE | Introduction -- CHAPTER TWO | The Narthex -- CHAPTER THREE | The Nave -- CHAPTER FOUR | The Transept -- CHAPTER FIVE | The Sanctuary -- CHAPTER SIX | The Radiating Chapels -- CHAPTER SEVEN | The Apsidal Chapels -- Notes -- Index.